2020
DOI: 10.3390/nu12061841
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Redox Equilibrium in the Pathogenesis of Psoriasis—Impact of Antioxidant-Rich Diet

Abstract: Psoriasis is a common, chronic, hyperproliferative, inflammatory skin disease occurring in most ethnic groups in the world. The disease is hereditary but the process of its inheritance is complex and still not fully understood. At the same time, it has been observed that psoriatic lesions may be triggered by certain prooxidative external factors: using narcotics, smoking, drinking alcohol, physical and mental stress, as well as bacterial infections and injury. Since the main physiological marker of psoriasis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 158 publications
0
17
0
Order By: Relevance
“…Maintaining a correct diet by eliminating some foods and including others can limit the release of such antibodies if the comorbidity is confirmed, thus contributing to the overall improvement of the diabetes patient's health. The positive effects of tea consumption on the health of patients with various autoimmune diseases have been confirmed in numerous studies [5,65,149,174,175].…”
Section: Immunomodulatory Activitymentioning
confidence: 80%
See 1 more Smart Citation
“…Maintaining a correct diet by eliminating some foods and including others can limit the release of such antibodies if the comorbidity is confirmed, thus contributing to the overall improvement of the diabetes patient's health. The positive effects of tea consumption on the health of patients with various autoimmune diseases have been confirmed in numerous studies [5,65,149,174,175].…”
Section: Immunomodulatory Activitymentioning
confidence: 80%
“…Mitochondria are the main source of oxidative stress in diabetes [49,64]. During oxidative metabolism, mitochondria reduce oxygen to H 2 O, while any excess oxygen is converted into reactive oxygen species O•, and then into peroxynitrite ONOO−, hydroxy radical OH•, and hydrogen peroxide H 2 O 2 [46,48,65]. Additionally, the lipids of mitochondrial membranes are susceptible to damage.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…EGCG belongs to the flavonoids. Its high concentration is found in green tea, quercetin, theaflavin, and thearubigin, present in black tea, as well as tannic acid [ 139 ]. It has been reported that EGCG possesses many benefits.…”
Section: Substances Of Natural Origin—plants and Phytochemicals With ...mentioning
confidence: 99%
“…Reports have shown that a diet rich in vitamin C, β-carotene, and flavonoids, which includes green vegetables, carrots, tomatoes, and fruit, helps improve skin lesions [ 6 , 34 ]. Therefore, persons with psoriasis should increase the intake of fresh fruit and vegetables as well as include polyphenol-rich products such as tea, coffee, herbs, and spices in their diet [ 47 ].…”
Section: The Importance Of Antioxidantsmentioning
confidence: 99%